Accounting and Finance Innovations 2021
DOI: 10.5772/intechopen.96791
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Effect of Bitcoin Halving Events on the U.S. Capital Market

Abstract: Bitcoin is a digital asset that was first mined in January 2009 after the global financial crisis of 2007–2008. Over a decade later, there is still no consensus across different market regulations on the classification, use cases, policies, and economic implications of bitcoin. However, there is an increasing demand for digital currency, as an alternative to fiat currency which would spur financial innovation and inclusion. This study reviews regulations on digital assets across countries. It further discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Therefore, knowledgeable investors follow these transactions and have positions. Mahdy (2021) revealed that negative abnormal returns were obtained in the US stock market on the announcement days of the two halving events in Bitcoin in 2012 and 2016, and therefore the scarce supply of Bitcoin was harmful to the US capital market. Ante (2021) examined the effect of Elon Musk's seven tweets related to Bitcoin and Dogecoin in 2020 and 2021 on the transaction volumes of related cryptocurrencies and revealed that each tweet is associated with abnormal transactions volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, knowledgeable investors follow these transactions and have positions. Mahdy (2021) revealed that negative abnormal returns were obtained in the US stock market on the announcement days of the two halving events in Bitcoin in 2012 and 2016, and therefore the scarce supply of Bitcoin was harmful to the US capital market. Ante (2021) examined the effect of Elon Musk's seven tweets related to Bitcoin and Dogecoin in 2020 and 2021 on the transaction volumes of related cryptocurrencies and revealed that each tweet is associated with abnormal transactions volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These events have a profound impact on the supply of new Bitcoin entering circulation, leading to discussions and debates about their implications for the market (El Mahdy 2021;Masters 2019;Meynkhard 2019;Pan et al 2020;Patel 2021;Ramadhani 2022;Schär 2020). Understanding the dynamics of Bitcoin halving events is crucial for grasping the broader trends in the cryptocurrency landscape and anticipating potential price movements.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of Bitcoin halving has been a subject of extensive research and analysis within the cryptocurrency community, attracting the attention of scholars, economists, and market analysts. Several studies (binance 2024; bitpanda 2024; Chan et al 2023;Chaturved 2024;Coinbase 2024;CoinDCX 2024;Conway 2024;Crawley 2020;Cuthbertson 2024;El Mahdy 2021;ET Spotlight Team 2024;Howcroft and Wilkes 2024;Kuhn 2024;Masters 2019;M'bakob 2024;Meynkhard 2019;Pan et al 2020;Patel 2021;Ramadhani 2022;Samizadeh 2024aSamizadeh , 2024bSchär 2020;Singla et al 2023;Valamontes 2024;Whittaker 2024;ig 2024;Zhao 2024) have explored the implications of halving events on the supply dynamics, price stability, and market sentiment of Bitcoin. Conway (Conway 2024) and many other experts (Coinbase 2024;CoinDCX 2024;Cuthbertson 2024;ET Spotlight Team 2024;Jahanshahloo et al 2023;Meynkhard 2019;Schär 2020) emphasise that the Bitcoin halving is when Bitcoin's mining reward splits in half.…”
Section: Introductionmentioning
confidence: 99%
“…Whoever deciphers this will get the reward, provided that the rest of the members of the network confirm that the answer is correct. Currently, 6.25 Bitcoins are obtained for each new block validated; this is due to the third Bitcoin halving that took place on 11 May 2020 [14]. We must consider that to this fixed amount of Bitcoins are added the commissions for each of the transactions.…”
Section: Introductionmentioning
confidence: 99%